Novel cellular signatures for determining time since deposition for trace DNA evidence. (December 2022) - Ingram, Sarah; Philpott, M. Katherine; Ehrhardt, Christopher J.
Abstract: With the increase in sensitivity of DNA profiling, questions about how and when the DNA was deposited have become a driving issue in forensic cases. To address this, we propose a novel method to determine time since deposition of trace DNA samples based on morphological and autofluorescence properties of individual epithelial cells which can change as the sample ages. To develop this signature, a series of trace DNA samples were generated by contact/handling a substrate and then allowed to age anywhere between one day and more than one year prior to collection. Imaging flow cytometry (IFC) was then used to characterize the morphology and autofluorescence profiles of individual cells within each sample followed by multivariate modelling and predictive classification. Results: showed that epithelial cell populations could be classified with high accuracy (∼90%) into one of three time-since-deposition groups: < 1 week, between 1 week and 2 months, and > 2months. Differences across age groups were largely driven by decreases in brightfield contrast and increases in the intensity of autofluorescence. To further test this approach for forensic casework, 47 individual donor cell populations spanning each time deposition group were classified blindly against the remaining data set. Samples containing at least 75 cells and a posterior probability greater than 0.90 showed classification accuracies ∼95%. Accuracies for individual time groups were 97% (<1 week), 92% (1week-2months), 98% (>2 months) with an average posterior probability for all time groups ∼0.96. This indicates that autofluorescence and morphological analyses may provide probative information regarding time since deposition for many types of trace DNA samples in forensic casework.